Recordkeeping cultures - Oliver, Gillian; Foscarini, Fiorella (Facet books for archivists and records managers, 2020)
Recordkeeping Cultures explores how an understanding of organisational information culture provides the insight necessary for the development and promotion of sound recordkeeping practices.